Natural fermentation of bitter gourd (Momordica charantia) and noni fruit (Morinda citrifolia) in honey increases total phenol, total flavonoid, and antioxidant activity - Guardiola Esther Natalia; Sumitro Sutiman Bambang; Widyarti Sri (BIO Web of Conferences)
It is well known that bitter gourd and noni fruit contain high levels of beneficial chemicals, but tastes and flavour are less appealing. Due to enzymatic transformation, fermentation can change bioactive compounds that minimize bad taste and unpleasant odor. This study aimed to assess the phenol and flavonoid content and antioxidant activity of bitter gourd (Momordica charantia L.) and noni fruit (Morinda citrifolia) during fermentation in honey. Blendered-bitter gourd (BG) or noni fruit (NF) each is mixed with honey and distilled water in a ratio of 3:1:10, then fermented for 90 days at room temperature and anaerobic conditions. Total phenol (TPC), total flavonoid content (TFC), and antioxidant activity were measured every two weeks. TPC in fermented NF increased from 56.62 mg GAE/gr to 156.59 GAE in the 6-week. TPC in BG increased from 56.96 GAE/g to 146.39 GAE/g during 12-week fermentation. TFC of fermented NF increased from 4.55 mg QC/g to 12.92 mg QC/g in 12-week fermentation. TFC of fermented BG increased from 9.86 QC/g to 41.69 QC/g in 12 weeks of fermentation. The antioxidant activity of fermented BM and BP showed the highest antioxidant activity in the 6-week (0,574 mg TEAC/g and 0.528 mg TEAC/g). The results indicate that fermentation in honey can increase total phenol and flavonoid content, and the antioxidant activity of bitter gourd and noni fruit.